Pedagogical conditions for preparing future music teachers for active work with students in primary grades: (using contemporary art-pedagogical methodologies as examples) - Panasenko, Yuliia (Professional Art Education, 2024)
The article reveals the pedagogical conditions for preparing future music teachers for active work with students in the primary grades of the New Ukrainian School (NUS) through modern art-pedagogical methods. The concepts of "pedagogical conditions," "art pedagogy," "methodology," and "method" are identified. The pedagogical conditions affecting the process of preparing future music teachers for active work with students in the primary grades of the NUS through modern art-pedagogical methods are clarified. The pedagogical conditions for preparing future music teachers for active work with students in the primary grades of the NUS through modern art-pedagogical methods are outlined, including the integration of art into the educational process, the development of students’ creative abilities, the use of innovative technologies, and continuous self-improvement. It is established that one of the key conditions for the successful preparation of future music teachers is their ability and desire to integrate art into the educational process. Modern art-pedagogical methods, such as game activity methodology, music therapy, and project method, allow for the creation of a favorable atmosphere for learning music in the primary grades. Future teachers must be prepared to creatively use these methods and to seek new ways to implement art in the educational process. An important pedagogical condition is also the development of students’ creative abilities through music. Future teachers should have knowledge of methods to stimulate children’s creativity and the skills to apply them in practice. Such methods include interactive musical communication, the use of various musical instruments in the educational process, and encouraging students to engage in independent creative processes. Pedagogical conditions examined include: 1) creating a special creative environment that helps students recognize the value, necessity, and importance of applying art-pedagogical methods in primary school; 2) forming the necessary knowledge, skills, and abilities for future teachers to use art-pedagogical methods in their professional activities. The pedagogical conditions for preparing future music teachers for active work with students in the primary grades of the NUS through modern art-pedagogical methods are characterized. Object. The aim of the article is to reveal the pedagogical conditions for preparing future music teachers for active work with students in the primary grades of the New Ukrainian School (NUS) through modern art-pedagogical methods. The concepts of "pedagogical conditions," "art pedagogy," "methodology," and "method" are identified. The pedagogical conditions that influence the process of preparing future music teachers for active work with students in the primary grades of the NUS through modern art-pedagogical methods are clarified. The pedagogical conditions for preparing future music teachers for active work with students in the primary grades of the NUS through modern art-pedagogical methods are outlined, including the integration of art into the educational process, the development of students’ creative abilities, the use of innovative technologies, and continuous self-improvement. The article examines pedagogical conditions such as: 1) сreating a special creative environment that helps students recognize the value, necessity, and importance of applying art-pedagogical methods in primary school; 2) forming the necessary knowledge, skills, and abilities for future teachers to use art-pedagogical methods in their professional activities. The pedagogical conditions for preparing future music teachers for active work with students in the primary grades of the NUS through modern art-pedagogical methods are characterized. Methods & methodology. Traditional research methods were applied: conventional analysis of scientific and pedagogical literature, and empirical methods. During the study, the pedagogical conditions for preparing future music teachers for active work with students in the primary grades of the New Ukrainian School (NUS) using modern art-pedagogical methods were theoretically characterized. Among the identified pedagogical conditions were the integration of art into the educational process, the development of students’ creative abilities, the use of innovative technologies, continuous self-improvement, the creation of a special creative environment to help students understand the value, necessity, and importance of applying art-pedagogical methods in primary school, and the formation of the necessary knowledge, skills, and abilities for future teachers to use art-pedagogical methods in their professional activities. Results. The article explores the pedagogical conditions for preparing future music teachers to work actively with students in the primary grades of the New Ukrainian School (NUS) using modern art-pedagogical methods. The concepts of "pedagogical conditions," "art pedagogy," "methodology," and "method" are defined. "Pedagogical conditions" refer to the circumstances on which the implementation of the educational process depends. Art pedagogy is a specialized field of pedagogy that uses art (such as painting, music, dance, theater, literature, and others) as a tool for education, training, and development. The main goal of art pedagogy is to stimulate creativity, self-expression, emotional and social development, and to nurture the individual [Pavlyuk, 2013, p. 69]. The concept of "methodology" denotes specific principles, forms, and means of using methods to gain a deeper understanding of various pedagogical problems and their solutions [Busel V. 2005, с.664]. In didactics, "method" is seen as the collaboration between teacher and students, aimed at the sequential use of various means to achieve a specific goal through the exploration of educational material. The pedagogical conditions affecting the process of preparing future music teachers to work actively with students in the primary grades of the NUS using modern art-pedagogical methods have been identified. The pedagogical conditions for preparing future music teachers to work actively with students in the primary grades of the NUS using modern art-pedagogical methods have been outlined. These include the integration of art into the educational process, the development of students’ creative abilities, the use of innovative technologies, and continuous self-improvement. The pedagogical conditions considered include: 1) the creation of a special creative environment that helps students understand the value, necessity, and importance of applying art-pedagogical methods in primary school; 2) the formation of the necessary knowledge, skills, and abilities for future teachers to use art-pedagogical methods in their professional activities. The pedagogical conditions for preparing future music teachers to work actively with students in the primary grades of the NUS using modern art-pedagogical methods have been characterized. Conclusions. Among the pedagogical conditions for preparing future music teachers to work actively with students in the primary grades of the New Ukrainian School (NUS) using modern art-pedagogical methods, we can identify the integration of art into the educational process, the development of students’ creative abilities, the use of innovative technologies, continuous self-improvement, the creation of a special creative environment that helps students understand the value, necessity, and importance of applying art-pedagogical methods in primary school, and the formation of the necessary knowledge, skills, and abilities for future teachers to use art-pedagogical methods in their professional activities.